2019
DOI: 10.3390/nu11081892
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Nervonic Acid in Human Milk in the First 30 Days of Lactation: Influence of Lactation Stages and Comparison with Infant Formulae

Abstract: Nervonic acid (24:1 n-9, NA) plays a crucial role in the development of white matter, and it occurs naturally in human milk. This study aims to quantify NA in human milk at different lactation stages and compare it with the NA measured in infant formulae. With this information, optimal nutritional interventions for infants, especially newborns, can be determined. In this study, an absolute detection method that uses experimentally derived standard curves and methyl tricosanoate as the internal standard was dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 56 publications
1
16
0
Order By: Relevance
“…NA plays a vital role in developing and maintaining the brain and biosynthesizing and improving nerve cells. NA is a natural component of maternal milk and can promote infant growth by assisting nervous system development ( Farquharson et al, 1996 ; Ntoumani et al, 2013 ; Yu et al, 2019 ). Decreased NA levels are closely associated with a high risk of developing psychotic disorders in individuals ( Coupland and Raoul, 2001 ; Amminger et al, 2012 ; Vozella et al, 2017 ), and supplementation with NA is an established effective treatment for symptoms of several neurological diseases, such as demyelinating disorders ( Sargent et al, 1994 ; Vozella et al, 2017 ; Lewkowicz et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…NA plays a vital role in developing and maintaining the brain and biosynthesizing and improving nerve cells. NA is a natural component of maternal milk and can promote infant growth by assisting nervous system development ( Farquharson et al, 1996 ; Ntoumani et al, 2013 ; Yu et al, 2019 ). Decreased NA levels are closely associated with a high risk of developing psychotic disorders in individuals ( Coupland and Raoul, 2001 ; Amminger et al, 2012 ; Vozella et al, 2017 ), and supplementation with NA is an established effective treatment for symptoms of several neurological diseases, such as demyelinating disorders ( Sargent et al, 1994 ; Vozella et al, 2017 ; Lewkowicz et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Newborn infants obtain NA from breast milk. The NA concentration in human breast milk markedly decreases as lactation stages progress; its concentration in colostrum has been found to range from two-to six-fold higher than the concentration in mature milk 22 . A low level of NA is present in infant formula; therefore, it has been suggested that the content of NA in infant formula for newborns or premature infants should be increased 22 24 .…”
Section: Discussionmentioning
confidence: 97%
“…The vast territory of China leads to an abundant diet, which could influence the lipids in human milk. However, previous studies researched the influence of the lactation stage and regional diversity on the fatty acid composition, and rare studies reported the relationship to TAG composition (12,13).…”
Section: Introductionmentioning
confidence: 99%